Endogenous tetrahydrobiopterin in humans: circadian rhythm, sex, race, age, and disease status - Gao, Lan; Smith, Neil; Kong, Ronald (Frontiers in Pharmacology, 2025)
Introduction6R-L-erythro-5,6,7,8-tetrahydrobiopterin (BH4) is an essential cofactor for multiple enzymes, including phenylalanine hydroxylase (PAH). Exogenous BH4, or its natural precursor sepiapterin, is utilized to treat patients with phenylketonuria (PKU), a disease caused by PAH deficiency. This study aims to investigate correlation of endogenous BH4 concentrations with related factors, circadian rhythm, sex, race, age, and disease status.MethodsPredose or placebo treatment blood samples were collected in eight sepiapterin clinical trials from healthy adults and patients of all ages with PKU or primary tetrahydrobiopterin deficiency (PBD) to measure plasma BH4 concentrations. Graphic visualization, descriptive statistics, and analysis of variance were used to explore the relationship between participant characteristics and BH4 concentrations.ResultsIn total, 1175 BH4 measurements from 236 participants were analyzed, revealing a circadian rhythm of BH4 concentration. In healthy adults, BH4 had the lowest concentrations between 7:00 and 10:59 (geometric mean 2.06 ng/mL) and the highest between 19:00 and 22:59 (2.72 ng/mL). Asian participants exhibited the highest BH4 concentration (2.33 ng/mL), whereas comparable levels were observed in Whites and Blacks or African Americans (2.01 and 2.07 ng/mL, respectively). Endogenous BH4 in PBD patients was <0.5 ng/mL, while it was significantly higher in PKU patients (9.63 ng/mL for those >2 years). No age-dependent BH4 change was observed in healthy adults and participants with PKU >2 years. BH4 concentrations were higher in healthy adult males (2.18 ng/mL) than females (1.95 ng/mL), but not distinguishable between male and female patients with PKU.ConclusionCircadian rhythm and significant differences between sexes and races in BH4 concentrations were observed in healthy adults. BH4 concentrations do not change with age in healthy adults and PKU patients >2 years. BH4 concentrations were relatively stable between 7:00 and 10:59, providing a window for measurements with minimal variation. The significant difference in BH4 concentrations between patients with PBD, patients with PKU, and healthy adults could be utilized as a diagnostic tool.